2015
DOI: 10.1108/tg-05-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

Transforming fire prevention: a case study

Abstract: Purpose:The purpose of the research project was to examine the transformation of fire prevention processes via improved targeting of fire prevention interventions over a four year period.Design / methodology / approach: A four year case study of the transformation of fire prevention processes involving a UK fire and rescue service, local council, NHS primary care trust and a police force was undertaken.Findings: Understanding the socio-economic causal factors underlying unintentional dwelling fires, and the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Different population segments can have different levels and types of fire risk associated with them [38], [20]. Different population behaviours and lifestyles can also impact the level of fire risk [10], [37].…”
Section: Introductionmentioning
confidence: 99%
“…Different population segments can have different levels and types of fire risk associated with them [38], [20]. Different population behaviours and lifestyles can also impact the level of fire risk [10], [37].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, fire prevention approaches tended to utilise spatial analysis, based upon the numbers of accidental dwelling fires in different areas, or spatial modelling based upon the numbers or percentages of more at risk individuals such as the elderly, smokers, and binge drinkers in different geographical areas [12][13][14]. Other approaches to targeting fire prevention have utilised community modelling in order to better understand the different communities in an area, and their level of fire risk [15][16][17]. Runefors et al [18] examined the effectiveness of specific fire prevention measures for different population groups in a study in Sweden and concluded that the effectiveness of different fire preventive measures depends upon on age, gender, occupancy type, whether an individual is living alone and whether the individual is a smoker.…”
Section: Fire Prevention Targetingmentioning
confidence: 99%
“…Residential fires can be categorized in several ways, for example by fire ignition or fire losses, or by human or non-human action [38][39][40]. In this study, the residential fires registered by the rescue services in Swedish metropolitan areas are classified into three main groups or types depending on their causes [22].…”
Section: Types Of Residential Firesmentioning
confidence: 99%